Strategi Pemasaran Produk Al Multazam Group Dalam Meningkatkan Jumlah Calon Jamaah Selama Pandemi Covid-19 - Taufik Hidayat (Multazam : Jurnal Manajemen Haji dan Umrah, 2022)
This study aimed to examine the Al Multazam Group's marketing strategy and efforts to boost the number of potential pilgrims during the Covid-19 pandemic. This study method is qualitative descriptive research based on field research (field research). According to the findings of this study, Al Multazam Group's marketing approach for raising the number of prospective pilgrims during the Covid-19 pandemic utilized a marketing mix strategy (Product Strategy, Price Strategy, Place Strategy, and Promotion Strategy). In addition, Al Multazam Group undertakes internal and external environmental analysis, establishes short- and long-term goals, socializes products with partners and branches, and communicates with the congregation.